Avaliação da calibração do modelo Soil And Water Assessment Tool para a simulação de estradas não pavimentadas em bacias hidrográficas - Tesch, Fillipe (2015)
The solution to problems related to water resources have been based mainly on mathematical models used as integrated planning tools for natural resources. In this context, the Soil and Water Assessment Tool - SWAT model has been applied to several watersheds that need solution for problems including quality and quantity of water and management of the land use. In Brazil and in the State of Espírito Santo one of the biggest problems related to diffuse pollution in rural watersheds are the unpaved roads. The SWAT model has been widespread and researched in Brazil and is widely used by Brazilian universities, for modeling the water quantity and quality, as well as to plan the use, occupation and soil management. Considering that the management of unpaved roads must be entered on the agenda of the management of the use and occupation of the land, this project was dedicated to evaluate the calibration of the SWAT model for the simulation of unpaved roads on watersheds. It was chosen as the study area the Rio Perdido cachment, a direct tributary of the Rio Santa Maria do Doce basin. The SWAT model was applied in two scenarios: the first scenario disregarded the existence of unpaved roads in the basin; and the second scenario, in turn, considered the existence of unpaved roads as part of the use and occupation of the watershed. The modeled scenarios were calibrated from the SWAT- CUP calibration software. Calibration results indicated that scenario 1 showed much higher performance than scenario 2, especially in the case of sedimentology modelling. In general, both scenario 1 and scenario 2 showed poor performance for the simulation of small magnitude flows. The model showed better performance for calibration of flow mesurements that were more frequent over the monitored period. Finally, the simulation of unpaved roads in watersheds by SWAT model requires a greater effort in monitoring and performing tests for physical characterization of the hydrological conditions of the roads, facilitating the definition of the parameters required by the model.